2020
DOI: 10.3389/fpls.2020.00311
|View full text |Cite
|
Sign up to set email alerts
|

NO and ABA Interaction Regulates Tuber Dormancy and Sprouting in Potato

Abstract: In plants, nitric oxide synthase (NOS)-like or nitrate reductase (NR) produces nitric oxide (NO), which is involved in releasing seed dormancy. However, its mechanism of effect in potato remains unclear. In this study, spraying 40 µM sodium nitroprusside (SNP), an exogenous NO donor, quickly broke tuber dormancy and efficiently promoted tuber sprouting, whereas 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3oxide (c-PTIO), an NO scavenger, repressed the influence of NO on tuber sprouting. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 60 publications
(79 reference statements)
3
20
0
Order By: Relevance
“…Nitrogenous compounds, such as nitrate, NO and cyanide, have a positive effect on the release of dormancy [39][40][41]. Wang reported that the application of nitrate in potato promoted the expression of a gene involved in ABA catabolism (StCYP707A1) [42]. Nitrate acted as a signal regulating substance rather than a nutrient that reduced the level of dormancy.…”
Section: Plant Growth Regulators Regulation On Plant Seed Germinationmentioning
confidence: 99%
“…Nitrogenous compounds, such as nitrate, NO and cyanide, have a positive effect on the release of dormancy [39][40][41]. Wang reported that the application of nitrate in potato promoted the expression of a gene involved in ABA catabolism (StCYP707A1) [42]. Nitrate acted as a signal regulating substance rather than a nutrient that reduced the level of dormancy.…”
Section: Plant Growth Regulators Regulation On Plant Seed Germinationmentioning
confidence: 99%
“…Alkaloid intake in small quantities can lead to gastrointestinal symptoms, such as abdominal pain, vomiting, and diarrhea, whereas higher alkaloid doses can cause acute poisoning or severe symptoms, such as coma, neurological disorders, cardiac failure, and paralysis (Mensinga et al, 2005 ). Our results showed that ClO 2 could improve the antioxidant capacity and the safety of potato tubers by promoting the accumulation of flavonoids and inhibiting the synthesis of alkaloids, respectively (Deng et al, 2020 ; Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…During the potato storage in the fresh food market, or storage of tubers for seed harvesting and industrial processing, sudden sprouting occurs (Teper-Bamnolker et al, 2010 ). Tuber sprouting is controlled by several factors, such as plant hormones, genetic factors, signaling molecules, genotype, temperature, and other storage conditions (Wang et al, 2020 ). Sprouting is also determined by metabolic activities that regulate phytohormones to exert growth control (Sonnewald, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O 2 is regarded as a signaling molecule that regulates the dormancy process [ 58 ]. The H 2 O 2 level in dormant buds gradually increased with dormancy onset and decreased rapidly with dormancy release in perennial deciduous trees [ 31 ].…”
Section: Discussionmentioning
confidence: 99%